2020
DOI: 10.3390/biomedicines8100409
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Endoplasmic Reticulum Stress and Large Extracellular Vesicles (Microparticles) in Endothelial Cell Dysfunction

Abstract: Upon increased demand for protein synthesis, accumulation of misfolded and/or unfolded proteins within the endoplasmic reticulum (ER), a pro-survival response is activated termed unfolded protein response (UPR), aiming at restoring the proper function of the ER. Prolonged activation of the UPR leads, however, to ER stress, a cellular state that contributes to the pathogenesis of various chronic diseases including obesity and diabetes. ER stress response by itself can result in endothelial dysfunction, a hallma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 115 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…One study using a pancreatic β-cell line (INS-1 cells) demonstrated that RLX behaves as both an estrogen receptor antagonist through nuclear estrogen response element-dependent actions and as an estrogen receptor agonist by suppressing triglyceride accumulation [ 30 ]. The endoplasmic reticulum (ER) regulates intracellular calcium concentrations and protein folding and trafficking [ 31 , 32 , 33 , 34 ]. ER stress, the disruption of these ER functions, is related to T2DM in humans [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study using a pancreatic β-cell line (INS-1 cells) demonstrated that RLX behaves as both an estrogen receptor antagonist through nuclear estrogen response element-dependent actions and as an estrogen receptor agonist by suppressing triglyceride accumulation [ 30 ]. The endoplasmic reticulum (ER) regulates intracellular calcium concentrations and protein folding and trafficking [ 31 , 32 , 33 , 34 ]. ER stress, the disruption of these ER functions, is related to T2DM in humans [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide a new perspective on the mechanism of exercise intervention. EVs in circulation are closely associated with multiple systems during physical activity and may include stem cell-derived vesicles, platelet-derived vesicles, pro-coagulant EVs, and cardiovascular-associated vesicles [ 21 , 28 - 30 ]. Further studies examining exercise-mediated EV release and EV-mediated signaling pathways may be useful for exploring new avenues for chronic disease treatment and clinical diagnosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…525 endothelial activation and damage. They are excreted from endotheliocytes in response to inflammation [22]. Hatha yoga training is proposed as prophylaxis of metabolic syndrome.…”
Section: It Is Well Established Preventive Role Of Edhf In Vascular Dysfunctionmentioning
confidence: 99%